Horizontally Acquired Polysaccharide-Synthetic Gene Cluster From Weissella cibaria Boosts the Probiotic Property of Lactiplantibacillus plantarum - Gao, Yuqi; Niu, Mingze; Yu, Xiaohui; Bao, Tingting; Wu, Zhaowei; Zhao, Xin (Frontiers in Microbiology, 2021)
Lactiplantibacillus plantarum are probiotic bacteria, maintaining the integrity of the gastrointestinal epithelial barrier and preventing the infection of pathogenic bacteria. Exopolysaccharides (EPSs) are often involved in the probiotic property of L. plantarum. Here, we identified a new EPS-synthetic gene cluster, cpsWc, carrying 13 genes, laid on a large plasmid in a well-characterized probiotic L. plantarum strain LTC-113. The cpsWc gene cluster was horizontally acquired from Weissella cibaria, enhancing the biofilm formation ability of the host strain and its tolerance to harsh environmental stresses, including heat, acid, and bile. Transfer of cpsWc also conferred the probiotic properties to other L. plantarum strains. Moreover, cpsWc strengthened the adhesion of LTC-113 to intestinal epithelial cells. Both the cpsWc-carrying LTC-113 and its EPSs per se effectively attenuated the LPS-induced pro-inflammatory effect of intestinal epithelial cells, and inhibited the adhesion of pathogenic bacteria, such as S. typhimurium and E. coli by exclusion and competition. The newly identified cpsWc gene cluster emphasized the contribution of mobile EPS-synthetic element on the probiotic activity of L. plantarum, and shed a light on the engineering of probiotic bacteria.